THE IMPORTANCE OF HUMAN RESOURCE (HR) TRAINING IN MEDICAL FACULTIES AT DUHOK UNIVERSITY: AN ADMINISTRATIVE STAFF PERSPECTIVE - ABDAL, WASAN GAZI; RASHEED, AWAZ MAJEED (Journal of Duhok University, 2023)
medical faculties of Duhok University from the perspective of the administrative staff in those faculties. By adopting quantitative and descriptive-analytical approaches, the researcher could meet the intended objective. The population is represented in all the human resources working at the medical faculties of Duhok University. As for the sample, it was chosen randomly from the administrative staff working in the medical faculties at the targeted university. Those faculties include faculty of medicine, faculty of dentistry, faculty of veterinary medicine, faculty of nursing, faculty of medical sciences, and faculty of pharmacy.  To be specific, after the researcher designed the questionnaire based on the relevant studies, she used Google form and created a link to allow the sample to access the questionnaire. Then, she uploaded the link to Facebook pages. The questionnaire forms were filled out by 84 employees from the administrative staff. Thus, 84 forms were analysed. After administering the collected data to SPSS software and analyzing it, it was found that the training provided to the human resources in the medical faculties of Duhok University is deemed significant and effective from the perspective of the administrative staff at those faculties. In addition, training HR leads to expanding the HR knowledge and improving their problem-solving skills. It also reduces the costs incurred by Duhok University and the duration needed for doing tasks by HR.  In addition, it supports the process of meeting the goals of Duhok University and implementing its policies and strategies